A gas stations location and their relationship with the operational characteristics of a road network (2015)
This research proposal applies geostatistical techniques to discover the relationship between the geographic locations of different gas stations and the operational characteristics offered by the transport network of the city of Manizales. This research is supported by basic information gathered for more than a year using GPS equipment (more than 18 million records). The time needed to get to gas stations is calculated as well as the spatial coverage in terms of population and area. Graphical results are obtained and these explain the time needed to get to a particular gas station. Quantitative comparisons are made among the different types of gas stations and the sectors of the city lacking gas stations coverage are established.